2016
DOI: 10.1007/s00270-016-1540-x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Arterial Embolization of the Prostate Through a Single Prostatic Artery: A Case Series

Abstract: Peri-prostatic shunts are frequent during PAE, carrying the risk of non-target embolization of penis/corpus cavernosum or rectum but also the potential advantage to irrigate the contralateral lobe. Sometimes, bilateral embolization is impossible, carrying the risk of limited clinical success. The possibility to reach contralateral prostatic territory from the ipsilateral prostatic artery (PA) and embolize it via peri/intra-prostatic anastomoses could be of interest in this situation. We describe a series of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Three months after the operation, the patient reported significant improvement, with IPSS of six and estimated prostate volume of 61 cc (44% volume reduction assessed by transabdominal ultrasound). example, severe atherosclerosis and tortuous anatomy which are frequently encountered in elderly population, [6] because we assume that unilateral embolization of the entire prostate blush is more effective than unilateral embolization of hemi-prostate only. More studies are required to consolidate our observation, bearing in mind that bilateral PAE is the standard practice and should always be attempted.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Three months after the operation, the patient reported significant improvement, with IPSS of six and estimated prostate volume of 61 cc (44% volume reduction assessed by transabdominal ultrasound). example, severe atherosclerosis and tortuous anatomy which are frequently encountered in elderly population, [6] because we assume that unilateral embolization of the entire prostate blush is more effective than unilateral embolization of hemi-prostate only. More studies are required to consolidate our observation, bearing in mind that bilateral PAE is the standard practice and should always be attempted.…”
Section: Case Reportmentioning
confidence: 99%
“…This is invaluable for patients who can only be catheterized unilaterally due to atherosclerosis or tortuous anatomy. [6]…”
Section: Introductionmentioning
confidence: 99%
“…This clinical suspicion has been investigated by Bilhim et al (8) in a retrospective analysis: poor outcomes were observed in the unilateral group compared to the bilateral one, even if no statistical significance was seen between the two groups. Bilateral PAE is feasible from a single-sided approach, due to intraprostatic anastomoses and the possibility to cross from one side to the other one (34). This technique may be considered in patients with occluded internal iliac artery on one side.…”
Section: Techniquementioning
confidence: 99%
“…Additionally, Figure 6C shows significant cross-filing of the right PA from the left PA. This allows for nearly complete embolization of the prostate from one side but can make identification of the contralateral PA difficult once the vessel is embolized [13].…”
Section: Atypical Origins Of the Pamentioning
confidence: 99%